Palynology of Permian-Triassic Boundary Beds at Kap Stosch, East Greenland. - Balme, B. E. (Meddelelser om Grønland, 1979)
Palynological studies have been carried out on Permian and Early Triassic sediments from Kap Stosch, East Greenland. Pollen grains and spinose acritarchs were present in all samples and abundant in most; spores were uncommon in the Permian. Thirty-three taxa have been illustrated and briefly described and Tympanicysta gen. nov. (type: T. stoschiana sp. nov.) has been instituted to accommodate certain inaperturate vesicles of unknown affinities. Permian assemblages, with abundant and diverse Vittatina, resemble those from Tatarian strata in northern European Russia. Two distinct plant microfossil associations occur in the Lower Triassic. One contains large numbers of Protohaploxypinus, Striatoabieites, Ephedripites, Taeniaesporites and Cycadopites and resembles Griesbachian assemblages described from Canada. It was found only in coarse arkosic sequences occurring south-east of Kap Stosch. Assemblages from the shale-carbonate succession exposed south-west of Kap Stosch are dominated by Taeniaesporites and lycopsid spores and are comparable to those from the Early Scythian of Pakistan, Malagasy and Western Australia. It is suggested that the arkosic succession is slightly older than the shale-carbonate sequence and should possibly be referred to a distinct formation. No palynological evidence indicates extensive reworking of the fine elastic Permian lithotopes developed at Kap Stosch into sediments of the overlying Lower Triassic.